Comparative evaluation of CBCT and MRI in Temporomandibular Joint (TMJ) disorders and their relationship to periodontal health - Neeldipsinh Jadeja; Amit K Sahu; Raksha Thakur; B Mohammed Ismail; K Hanumantha Kumar; K Sadananda; Dhaval N Mehta (Wolters Kluwer Medknow Publications, 2024)
Cone beam computed tomography (CBCT) and magnetic resonance imaging (MRI) are diagnostic tools frequently employed to evaluate temporomandibular joint (TMJ) disorders, yet their comparative efficacy remains a subject of interest. In this study, we conducted a comparative evaluation of CBCT and MRI in diagnosing TMJ disorders and assessing their association with periodontal health. We recruited a sample of 100 patients presenting with TMJ symptoms and divided them into two groups. Group A underwent CBCT imaging, while Group B received MRI scans. Clinical assessments of periodontal health were performed using established periodontal indices. Diagnostic accuracy, sensitivity, specificity, and interobserver agreement were calculated for each imaging modality. In the current study, CBCT demonstrated superior diagnostic accuracy (85%) compared to MRI (72%) in identifying TMJ disorders. Sensitivity and specificity for CBCT were 87% and 83%, respectively, while for MRI, sensitivity was 68%, and specificity was 76%. Interobserver agreement was substantial for CBCT (κ = 0.75) and moderate for MRI (κ = 0.56). In addition, CBCT revealed a significant correlation between TMJ disorders and periodontal health (P < 0.05), while MRI showed a weaker association (P < 0.1). We concluded from this study and suggest that CBCT is a more accurate imaging modality for diagnosing TMJ disorders compared to MRI. Moreover, CBCT provides valuable insights into the relationship between TMJ disorders and periodontal health, highlighting the importance of comprehensive dental assessments.